The Role of Institutions in Optimizing Employee Performance at the Dinas Ketahanan Pangan Pekanbaru City - Ramadina Safitri; Abdul Sadad (FISIP Universitas Malikussaleh, 2021)
This study aims to determine the role of institutions in achieving employee work optimization at the Dinas Ketahanan Pangan Kota Pekanbaru. Optimization is an action or process that makes something better and more effective. If optimization is associated with the role of institutions, then there are institutional norms that encourage the achievement of work optimization. This study used the Hardjanto indicators, namely equality, consensus orientation, participation, and responsiveness. The research method in this study is qualitative. The result shows that the Dinas Ketahanan Pangan Kota Pekanbaru encourages institutional role in running its organization. Leaders liven up certain norms such as giving every employee fair and equal rights and obligations following their duties and functions, prioritizing deliberation in the policy process, respecting active participation, and encouraging a responsive and serving work culture. Of the four indicators, the responsiveness dimension has not worked well, while the other three dimensions have been implemented properly.ABSTRAKPenelitian ini bertujuan untuk mengetahui peran kelembagaan dalam mencapai optimalisasi kerja pegawai pada Dinas Ketahanan Pangan Kota Pekanbaru. Optimalisasi adalah tindakan atau proses yang membuat sesuatu menjadi lebih baik dan lebih efektif. Jika optimalisasi dihubungkan dengan peran kelembagaan, maka ada norma-norma kelembagaan yang mendorong tercapainya optimalisasi kerja. Penelitian ini menggunakan indikator Hardjanto dimana peran kelembagaan ditentukan dari 4 dimensi yang melekat, yaitu equality, consensus orientation, participation, dan responsiveness. Metode penelitian dalam studi ini adalah kualitatif. Hasil penelitian yaitu Dinas Ketahanan Pangan Kota Pekanbaru menghidupkan peran kelembagaan yang kuat dalam menjalankan organisasinya. Pimpinan menghidupkan norma-norma tertentu seperti memberikan setiap pegawai hak dan kewajiban yang adil dan setara sesuai dengan tugas pokok dan fungsinya, mengedepankan musyawarah dalam proses kebijakan, menghargai partisipasi aktif, dan mendorong budaya kerja yang tanggap dan melayani. Dari keempat indikator tersebut, dimensi responsiveness belum berjalan dengan baik, sedangkan tiga dimensi yang lain sudah dijalankan sebagaimana mestinya.